(untitled) (The Spectrum, 2026)
This paper offers a comparative rhetorical analysis of Helen of Troy and Draupadi of the Mahabharata by examining how ancient literary traditions construct women as symbolic sites for negotiating blame, agency, and the legitimacy of war. Through a close reading of Gorgias’s Encomium of Helen, Isocrates’s Helen, Euripides’s Helen, and key episodes of Draupadi’s life from Mahabharata, including her polyandrous marriage, abductions, humiliation in the dice game, and subsequent political interventions, I argue that both figures function less as stable mythic women and more as rhetorical pretexts deployed by male authors to articulate their ideological concerns. The analysis reveals that in Greek rhetorical traditions, Helen becomes a medium for exploring persuasion, culpability, and civic pedagogy. In the Mahabharata, Draupadi’s assertive voice and ethical interventions reveal the tensions within patriarchal dharma and the political logic of epic violence. Despite their cultural and contextual differences, Helen and Draupadi serve analogous purposes: each becomes an instrument through which patriarchal systems negotiate honor, order, and the socio‑political justification of violence. The paper highlights their rhetorical functions over mythic ones by exploring how these figures become enduring sites of cultural meaning-making and suggests directions for analyzing their evolving reinterpretations in modern literature and media.